Populasi Mikroba Pada Saluran Cerna Ayam Pedaging yang diberi Probiotik dan Fitogenik sebagai Feed Additive dalam Ransum - Daud, Muhammad; Yaman, Muhammad Aman; Fuadi, Zahrul; Mulyadi, Mulyadi (Jurnal Sain Veteriner, 2024)
The aim of this study was to evaluate the population of lactic acid bacteria and pathogenic bacteria (Escherichia coli) in the gastrointestinal tract (duodenum, jejunum, ileum and cecum) of broiler chickens aged 2, 4 and 6 weeks given probiotics and phytogenics in the diet. The study used 96 day old chicks (DOC) which were reared up to the age of six weeks. The study was conducted using an experimental method, using a Completely Randomized Design (CRD) consisting of four ration treatments and four replications. The ration treatments consisted of: R1 (basal ration/control), R2 (basal ration + probiotic), R3 (basal ration + phytogenic), and R4 (basal ration + probiotic + phytogenic). The variables observed were the population of lactic acid bacteria and pathogenic bacteria (Escherichia coli) in the gastrointestinal tract/intestine of broiler chickens (doudenum, jejunum, ileum and cecum) aged 2, 4 and 6 weeks. Data analysis was carried out with one-way variance and continued with Duncan's Multiple Range Test. The results showed that the use of probiotics and phytogenics as feed additives in the diet significantly (P<0.05) increased the of lactic acid bacteria population and decreased the Escherichia coli population in the gastrointestinal tract of broiler chickens aged 2, 4 and 6 weeks of the study. It was concluded that the use of probiotics and phytogenics as feed additives in the ration could have a positive effect on the gastrointestinal tract of broilers.